Model analysis of traffic emergency dispatching in intelligent transportation system under cloud computing. Issue 1 (6th February 2020) - Song, Minglei; Hou, Zhixiang
Aiming at the problem of low traffic capacity and low scheduling throughput of traditional intelligent transportation system traffic emergency dispatching model, a traffic emergency dispatching model based on cloud computing for intelligent transportation system is proposed. On the basis of the established cloud computing system, a time-constrained traffic emergency scheduling model of the intelligent transportation system is established. The improved genetic algorithm is used to solve the model and obtain the optimal scheduling scheme. The experimental results show that the traffic capacity of the proposed method varies from 0 to 1.0, which can ensure the smooth traffic of the vehicle. When the traffic congestion is light, the vehicle throughput of the three scheduling models is not significantly different. In the case of congestion and heavy congestion, the throughput of the proposed method is always in the range of 0.4–0.8, and the scheduling performance is the best.